P.122 The Pediatric Neuroirritability Management Protocol at the Stollery Children's Hospital – Inspired by an Irritable Infant with GM3 Synthase Deficiency. (November 2021) - Ng, C; Rapoport, A; Rajapakse, T; Kassiri, J; Liu, N; Goez, H; Yager, J; Wren, T; Richer, L; Sinclair, D; Mailo, J
Abstract : Background: We describe an infant with a diagnosis of GM3 synthase deficiency, presenting with severe neuroirritability from birth. He required multiple admissions due to extreme agitation and caregiver burnout. Multiple pharmacological agents were tried, and the effect of each medication was modest and short-lasting at best. The literature on the management of neuroirritability in children with progressive genetic and metabolic conditions is sparse, and a neuroirritability management protocol has yet to be developed at our institution. Methods: We searched for relevant primary research and articles on PubMed. We reviewed the evidence of each pharmacological agent and added non-pharmacological strategies. We developed management guidelines for neuroirritability at our hospital. This protocol was reviewed by several pediatric neurologists and pediatric palliative care specialists at the Stollery and SickKids Hospitals. Results: We present the Pediatric Neuroirritability Management Protocol for the Stollery Children's Hospital. Conclusions: Further study is required to assess whether this protocol can be adapted to treat irritability in the context of other neurological conditions such as hypoxic-ischemic encephalopathy and non-accidental injury. In addition, we will expand our guidelines to include other symptoms such as spasticity, dystonia, and autonomic dysfunction.